The combined serum levels of miR-375 and urokinase plasminogen activator receptor are suggested as diagnostic and prognostic biomarkers in prostate cancer - Wach, Sven; Al-Janabi, Omar; Weigelt, Katrin; Fischer, Kersten; Greither, Thomas; Marcou, Marios; Theil, Gerit; Nolte, Elke; Holzhausen, Hans-Juergen; Stoehr, Robert; Huppert, Verena; Hartmann, Arndt; et al. (International Journal of Cancer, 2015)
This study aimed to assess the applicability of miR-375 in combination with the soluble urokinase plasminogen activator receptor (suPAR) protein as a diagnostic and/or prognostic biomarker for prostate cancer (PCa) patients. miR-375 levels by qRT-PCR and suPAR levels by ELISA were evaluated in serum samples from 146 PCa patients, 35 benign prostate hyperplasia (BPH) patients and 18 healthy controls. Antigen levels of suPAR differed between healthy controls and PCa or BPH patients, whereas miR-375 levels differed between PCa and BPH patients or healthy controls (p < 0.001). Additionally, suPAR levels differed between the Gleason sum groups GS = 7 versus GS > 7, with higher levels in the latter group (p = 0.011), and miR-375 levels were higher in the tumor stage group T3-T4 compared with the T1-T2 group (p = 0.039). A high concentration of suPAR was associated with a poor disease-specific survival (DSS; p = 0.039). The combination of suPAR and miR-375 levels identified a patient group possessing high levels for both parameters. This was associated with a poorer 10-year overall survival (OS) and DSS, with a 6.38-fold increased risk of death and a 7.68-fold increased risk of tumor-related death (p = 0.00026 and p = 0.014; univariate Cox's regression analysis). In a multivariate Cox's regression analysis PCa patients with high levels of suPAR and miR-375 showed a 5.72-fold increased risk of death in OS (p = 0.006). In summary, the differences between the PCa/BPH/healthy control cohorts for either suPAR and miR-375 levels in conjunction with the association of combined high suPAR/miR-375 levels with a poor prognosis suggest a diagnostic and prognostic impact for PCa patients.
EVALuna2:6726